Proposal for adaptation and conceptualization of the 40 triz inventive principles considering the use of additive manufacturing and design for additive manufacturing - Reis, Paulo Henrique Rodrigues Guilherme; Silveira, Carina Santos; Rosa, Fernanda Oliveira Santos; Soares, Lucas de Figueiredo; Souza, Nilmar de (Brazilian Journal of Production Engineering, 2024)
Among the methodologies for creating concepts for the development of new products, the TRIZ methodology (Theory of Inventive Problem Solving) is an efficient catalyst for generating ideas and solutions in product conception. Such solutions assist in resolving technical conflicts during the conceptualization stage of a new product or component. To ensure that the solutions proposed by this methodology are consistent with the context of engineering conflicts, it is necessary, in specific cases, to manufacture devices with complex and/or customized geometry. Conventional manufacturing processes may present substantial limitations in the production of these devices. Thus, to mitigate this limitation, this article proposes the association between the TRIZ methodology, Additive Manufacturing (AM), and Design for Additive Manufacturing (DfAM). As a result, this work presents a proposal for new terms adapted to the 40 classical inventive principles of the TRIZ methodology, considering the AM and DfAM perspectives, as well as their possibilities and limitations. Direct applications of the new adapted terms were defined according to the observed reality in the context of AM and DfAM.